Control, ideology and identity in civil war: the Angolan Central Highlands 1965-2002 - Pearce, J (2011)
This thesis examines the relationship between political movements and people during the civil war between Angola’s MPLA government and the UNITA rebels in the Central Highlands region. It shows how conflicting ideas about political legitimacy originating in anticolonial struggle informed leaders’ decisions and formed the basis of their efforts to politicise people. Much existing literature sees civil conflict in terms of rebellion against a state, motivated by grievance or by the desire for loot. I argue against such an approach in the Angolan case, since the MPLA and UNITA originated from different strands of nationalism, and neither achieved complete control over Angola’s territory and people. Instead, I draw on constructivist approaches to statehood in analysing the war as a contest in which both sides invoked ideas of the state in asserting their legitimacy. The MPLA state controlled the cities while UNITA established rural bases and a bush capital, Jamba. Violence, often involving the capture of people, occurred at the margins of the areas of influence. Within each zone, each movement controlled public discourse to make its control hegemonic. Each presented itself as the authentic representative of the Angolan nation and condemned the other movement as the agent of foreign interests. These nationalist claims were given substance by processes of state building, more fully realised by the MPLA than by UNITA. Each movement’s claim to statehood served to legitimise its own violence while criminalising the violence of the other side. Public dissent was prohibited in either zone, but people’s responses to politicisation ranged from genuine support, to co-operating only as necessary to avoid punishment, depending largely on their degree of involvement in the state building process. War itself was central to constituting perceptions of common interest, and political actors’ capacity to manipulate perceptions depended largely on military control.